Understanding Behavioral Intentions: How Customers Decide to Adopt Internet Banking in Bangladesh - Bipul Kumar Sarker; Debobrota Kumar Sarker; Shompa Rani Shaha; Deepongkar Saha; Saurav Sarker (goodwood publishing, 2024)
Purpose: In the arena of digital banking, internet banking has become a hotcake. As internet banking becomes an increasingly integral component of the financial services sector, understanding the determinants that drive or inhibit its adoption among active customers is crucial for both banks and policymakers. Research Methodology: The research employs a quantitative. A structured questionnaire were used to collect data from the customers, focusing on key constructs such as technological device self-efficacy (TSE), user-friendly (UF), beneficial (B) , security concerns (SC), features of the apps (FA), trust, social influence (SI). In this study answer sheets were provided to 350 banking service consumers out of which only 174 answered the questions. After discarding the incomplete answer sheets, a total of 146 were found suitable for the study. Statistical analyses, including descriptive analysis, correlation analysis and multiple regression, are applied to identify and quantify the relationships between these factors and behavioral intentions. Results: According to the findings, the intention of users to use internet banking services in Bangladesh was significantly predicted by the user-friendly (B = 0.708, t = 5.585; p < 0.000) and features of the applications (B = 0.392, t = 2.443; p < 0.016). On the other hand, in Bangladesh, the behavioral intention to use internet banking is most significantly impacted by user friendly. Limitations: The study is only geographically focused on Bangladesh and may ignore the influence of external factors (such as regulatory changes and economic fluctuations), which may significantly influence consumer adoption decisions. Contribution: The study will contribute to the academic literature by extending the existing theories of technology adoption in the context of internet banking in Bangladesh. The findings of this study will assist strategic decisions, policy formulation, and initiatives to promote greater adoption and effective use of Internet banking services.